Nursing perspective of gamma knife of treatment - parvaneh vasli (Journal of Holistic Nursing and Midwifery)
Gamma knife is a new noninvasive method for treatment of patient with brain tumors. ‎Another name of this procedure is steriotatic radiosurgery.‎‏ ‏This computerized advanced ‎technique was implicated by a team including neurosurgeon, neuroradialogist, oncologist, and ‎a nurse. This method is used for treatment of certain brain tumors and lesions. The benefits are ‎low risk of postoperative complication, no general anesthesia, high accuracy, safety and ‎rehabilitation, improved outcomes and faster return to home.‎ ‎ Four stage of this procedure include:‎ ‏1‏‎- frame placement ‏2‏‎- imaging ‏3‏‎- planning ‏4‏‎- Treatment A gamma knife nurse is usually the first person who communicates with the patient and is ‎present at patient s side before treatment until follow up. Nurse is also the liaison between ‎treatment team and patients. Their duties include maintaining effective relationship between ‎medical team, planning patient s treatment, cooperation with physician, providing nursing care ‎to patients, educating patients and their family and physical and mental support. ‎